Relationship between Entrepreneurial Characteristics from Islamic Perspective and the Performance of Small and Medium-Sized Businesses (A Study of SMEs in Indonesia) - Lisnawati, D; Eeng Ahman, H (KnE Social Sciences, 2019)
This study aims to analyze the relationship between entrepreneurial characteristics from Islamic perspective and the performance of SMEs of Muslim entrepreneurs in Indonesia. Factors suspected of affecting entrepreneurial characteristics from Islamic perspective are fathanah (wisdom), amanah (trustworthy), siddiq (truthfulness) and tabligh (advocacy). The study method used an explanatory survey with data collection techniques with technical questionnaires and interviews to 50 fashion muslim entrepreneurs in Bandung-West Java. The collected data is analyzed by using SPSS. The result from the study shows that Entrepreneurial characteristic from Islamic perspective has relationship with the performance of SMEs. This finding implies that in order to improve the performance of SMEs especally for Muslim entrepreneurs must be empowered their self to have the strong motivation to excel their potentials sources based on the Islamic teaching in Quran and Sunnah. Keywords: Entrepreneurial characteristic; Islamic entrepreneurship, Performance of SMEs; Fashion.